Dynamics and consequences: The economic/ecological double crisis in China and the bauxite-aluminium industry in Ghana - Sebastian Purwins (Spatial transformation: Processes, strategies, research design, 2022)
The economic/ecological double crisis has long since reached China. In order to stabilise the growing economy, access to new markets and resources is indispensable. At the same time, the associated environmental damage is steadily increasing, causing public pressure on the government in Beijing. This article argues that, in the sense of David Harvey (1982), crises are not solved, but rather spatially managed. Ghana as a market and the predominantly untapped bauxite reserves have aroused China's interest. In 2017, the two countries signed a Memorandum of Understanding concerning the development of an integrated bauxite-aluminium industry in Ghana. What may be interpreted as crisis management for China leads to an increased exploitation of natural resources in Ghana and to the problem of leaving this development path. Based on field research in March 2018 and intensive research on the literature, these dynamics and possible consequences are discussed here using the concept of the spatial fix and the economic/ecological double crisis.
urn:nbn:de:0156-08911180; hdl:10419/251347; https://econpapers.repec.org/RePEc:zbw:arlfob:19
Keywords: 710; China; development path; spatial fix; Ghana; bauxite-aluminium industry